PERAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MENGENTASKAN KEMISKINAN PERKOTAAN (STUDI KASUS PADA KOMUNITAS PUNK DI KOTA YOGYAKARTA) - Rila Setyaningsih (Universitas Muhammadiyah Jakarta, 2018)
The purpose of writing this article is to describe: (1) Background punk community, and (2) the roles of technology, information, and communication to alleviating the urban poverty of punk. The approach used in the study is a qualitative deskripstif. The research location is in the city of Yogyakarta. While, the study subjects were punks who come from disadvantaged backgrounds. Data collection techniques consisting of: (1) observation, (2) in-depth interviews, and (3) documentation. Analysis: (1) induction when in the field with the pattern of triangulation, (2) a holistic do after field. The results showed that: First, poverty can be the background of a person chooses to be a punk. Second, the role of technology, information, and communication is essential in alleviating the urban poverty, especially punk community in the city of Yogyakarta. Keywords: Technology information and communication, Urban poverty, Punk